First Aerial South Atlantic Night Crossing - Neves, Fernando M. S. P. (2015)
The history of the transatlantic flights began in 1919 when Albert C. Read’s team flew an NC-4 flight between Newfoundland and Lisbon, Portugal with a stopover at Azores Islands, for fuel and repairs. The flight was made following a chain of 70 US warships in order to guide it along its route and provide assistance if needed. Two weeks later, John Alcock and Sir Arthur Whitten Brown made the first nonstop transatlantic flight from Newfoundland to County Galway, Ireland, covering more than 3000 km in just 16 hours of flight. Gago Coutinho and Sacadura Cabral crossed the South Atlantic Ocean by air in 1922, using only internal means of navigation: a modified sextant and a course corrector. For the first time in the aviation history a transatlantic flight was accomplished using exclusively astronomical and estimated navigation processes. Both devices proved its effectiveness. In 2 March 1927 and by following all the knowledge obtained by the First Cross of the South Atlantic, Sarmento de Beires, Jorge Castilho, Duvalle Portugal and Manuel Gouveia started a new mission that became known as the First Aerial South Atlantic Night Cross. During the night of 16 to 17 March 1927 a Portuguese crew flew 2595 km over the Atlantic Ocean from Guinea, Africa to Fernando de Noronha Island, Brazil. The flight was made only by astronomical processes navigation resources that proved again to be absolutely feasible and trustworthy, regardless day or night lighting conditions.